Usefulness of clinical and laboratory parameters for differentiation of biliary atresia from idiopathic neonatal hepatitis: Experience in a tertiary care hospital of Bangladesh (Community Based Medical Journal, 2015)
Background: The two most common and important causes of neonatal cholestasis (NC) are biliary atresia (BA) and Idiopathic neonatal hepatitis (INH). There is no single test that can definitely differentiate these two entities.Objective: To evaluate the diagnostic accuracy of clinical and laboratory parameters for diagnosis of biliary atresia.Methods: This cross-sectional study was conducted at the department of Pediatric Gastroenterology and Nutrition of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from August 2013 through July 2015 among purposively sampled infants with neonatal cholestasis. Results: Total 86 neonatal cholestatic cases were studied. Term baby and good birth weight are significantly higher in BA cases. The presence of persistent pale colored stool is significantly more in patients with BA (p 0.000). GGT is the only liver enzyme that was found to be useful differentiating BA from INH at a cut-off value ≥ 524U/L or 9.5 times higher than upper limit normal with sensitivity and specificity of 81.6% and 72.9% respectively. In the present study the diagnostic accuracy of persistent pale colored stool found to be highest (79.1 %).Conclusion: The present study showed that Persistent pale colored stool and serum level of GGT with a cut-off value ≥524 U/L or 9.5 times higher than upper limit normal can be considered as predictive markers for differentiation of Biliary atresia from Idiopathic neonatal hepatitis.CBMJ 2015 January: Vol. 04 No. 01 P: 30-36